Unsteady aerodynamic and optimal kinematic analysis of a micro flapping wing rotor - Li, Hao; Guo, Shijun J.; Zhang, Y. L.; Zhou, C.; Wu, Jianghao (Elsevier, 2016)
Inspired by the high performance of rotary and insect flapping wings capable of vertical take-off and landing and hovering (VTOLH), a novel flapping wing rotor (FWR) has been developed by combining the above two types of wing motions. The FWR offers an alternative configuration for micro air vehicles (MAV) of such high flight performance. Unlike the well-studied aerodynamics of rotary and insect-like flapping wing with prescribed wing motion, the aerodynamic lift and efficiency of the FWR associated with optimal kinematics of motion has not been studied in a systematic manner before. This investigation is therefore focused on the FWR optimal kinematic motion in terms of aerodynamic lift and efficiency. Aerodynamic analysis is conducted for a FWR model of aspect ratio 3.6 and wing span 200 mm in a range of kinematic parameters. The analysis is based on a quasi-steady aerodynamic model with empirical coefficients and validated by CFD results at Re∼3500. For comparison purpose, the analysis includes rotary and insect-like flapping wings in hovering status with the FWR at an equilibrium rotation speed when the thrust equals to drag. The results show that the rotary wing has the greatest power efficiency but the smallest lift coefficient. Whereas the FWR can produce the greatest aerodynamic lift with power efficiency between rotary and insect-like flapping wings. The results provide a quantified guidance for design option of the three types of high performance MAVs together with the optimal kinematics of motion according to flight performance requirement.
Keywords: Bioinspired FWR; MAV; lapping wing; Optimal kinematics; Aerodynamic efficiency